Estimativas populacionais de jaguatiricas (Leopardus pardalis) e gatos-do-mato (Leopardus tigrinus) em duas unidades de conservação do Cerrado de Minas Gerais - Marcelo Juliano Rabelo Oliveira (2012)
The ocelot (Leopardus pardalis) and the tiger cat (Leopardus tigrinus) are two species of small cats that occur in the Cerrado. To address the gaps in knowledge for these species this thesis focused in evaluate their population status using camera-trap. Two protected areas in the Cerrado located in north/northern Minas Gerais were evaluated: Grande Sertão Veredas National Park (GSVNP) and Veredas do Peruaçu State Park (VPSP). Absolute abundance and density for so called closed populations were estimated for both species, also activity pattern and abundance index were calculated. Three adjacent areas (areas 1, 2 and 3) were evaluated in GSVNP. To experimentally assess the effect of a larger area data from these areas were analyzed separated and grouped. In area 1 five ocelot individuals were recorded and the estimated density was 0.08 indiv/km2. In this same area only one individual tiger cat was recorded. In area 2 three ocelot individuals were recorded and the estimated density was 0.04 NGSV indiv/km2. in this same area nine individuals of tiger cat were recorded and the estimated density was 0.29 indiv/km2. In area 3 ocelot was not recorded and only two individuals of tiger cat were recorded. When area 1 and 2 are grouped the ocelot density is 0.02 indiv/km2 and when all areas (1, 2 and 3) are grouped the estimated density for tiger cat is 0.13 indiv/km2. In VPSP two areas were evaluated (4 and 5). In area 4 two ocelots were recorded resulting in a density of 0.04 indiv/km2, the tiger cat was not recorded in this area. In area 5 only one individual of ocelot was recorded and seven individuals of tiger cat were recorded resulting in a density of 0.67 indiv/km2. The abundance index suggests a slightly higher probability of capture ocelots than tiger cats using camera-traps. The activity pattern for both species was mainly nocturnal with a positive correlation. The results were discussed in relation to the need of a an evaluated area large enough to conduct density estimates for these species. A possible inter-specific competition between the target species is also discussed, being observed a possible ecological release of tiger cats in an area where ocelot density is low.